Relationships between brain perfusion and early recanalization after intravenous thrombolysis for acute stroke with large vessel occlusion. Issue 3 (March 2020) - Seners, Pierre; Turc, Guillaume; Lion, Stéphanie; Cottier, Jean-Philippe; Cho, Tae-Hee; Arquizan, Caroline; Bracard, Serge; Ozsancak, Canan; Legrand, Laurence; Naggara, Olivier; Debiais, Séverine; Berthezene, Yves; et al.
In large vessel occlusion (LVO) stroke, it is unclear whether severity of ischemia is involved in early post-thrombolysis recanalization over and above thrombus site and length. Here we assessed the relationships between perfusion parameters and early recanalization following intravenous thrombolysis administration in LVO patients. From a multicenter registry, we identified 218 thrombolysed LVO patients referred for thrombectomy with both (i) pre-thrombolysis MRI, including diffusion-weighted imaging (DWI), T2*-imaging, MR-angiography and dynamic susceptibility-contrast perfusion-weighted imaging (PWI); and (ii) evaluation of recanalization on first angiographic run or non-invasive imaging ≤ 3 h from thrombolysis start. Infarct core volume on DWI, PWI-DWI mismatch volume and hypoperfusion intensity ratio (HIR; defined as Tmax ≥ 10 s volume/ Tmax ≥ 6 s volume, low HIR indicating milder hypoperfusion) were determined using a commercially available software. Early recanalization occurred in 34 (16%) patients, and multivariable analysis was associated with lower HIR ( P = 0.006), shorter thrombus on T2*-imaging ( P < 0.001) and more distal occlusion ( P = 0.006). However, the relationship between HIR and early recanalization was robust only for thrombus length <14 mm. In summary, the present study disclosed an association between lower HIR and early post-thrombolysis recanalization. Early post-thrombolysis recanalization is therefore determined not only by thrombus site and length but also by severity of ischemia.